1964
DOI: 10.1177/12.12.880
|View full text |Cite
|
Sign up to set email alerts
|

A HISTOCHEMICAL STUDY OF SUBSTRATE SPECIFICITY FOR THE STEROID 3β-ol DEHYDROGENASE AND ISOMERASE SYSTEMS IN HUMAN OVARY AND TESTIS

Abstract: Either the enzyme which oxidizes 3β-ol groups in C-19 and C-21 steroids is properly designated a steroid-3β-hydroxy dehydrogenase or there is a multiplicity of such dehydrogenases. Although DHA is a satisfactory substrate for the human ovary, adrenal, and placenta, it is not generally so for the human testis. Pregnenolone is only at times a moderately satisfactory substrate in the ovary and is not satisfactory for the testis. In the present histochemical study two Δ4,3β-ol steroids have been reported as sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1965
1965
1980
1980

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Nevertheless, using purified preparations of alcohol dehydro¬ genase it has been shown in vitro (Merritt & Tomkins, 1959) that steroids such as testosterone and cortisol are not attacked by this enzyme. Goldberg, Jones & Borkowf (1964) have reported a histochemical colour reaction in human Leydig cells with 3/?,17/?-dihydroxyandrost-4-ene (androstenediol), 3ahydroxy-5a-androstan-17-one and the dipropionate of androstenediol as substrates. While these workers attribute the diformazan deposition in their testicular sections to a reaction of 3/?-hydroxysteroid dehydrogenase with these steroids, it seems likely that part at least of the formazan deposition they describe arises from 17/?-hydroxy¬ steroid dehydrogenase activity and part from a steroid 5aor 5/?-dehydrogenase.…”
Section: Histochemical Considerationsmentioning
confidence: 99%
“…Nevertheless, using purified preparations of alcohol dehydro¬ genase it has been shown in vitro (Merritt & Tomkins, 1959) that steroids such as testosterone and cortisol are not attacked by this enzyme. Goldberg, Jones & Borkowf (1964) have reported a histochemical colour reaction in human Leydig cells with 3/?,17/?-dihydroxyandrost-4-ene (androstenediol), 3ahydroxy-5a-androstan-17-one and the dipropionate of androstenediol as substrates. While these workers attribute the diformazan deposition in their testicular sections to a reaction of 3/?-hydroxysteroid dehydrogenase with these steroids, it seems likely that part at least of the formazan deposition they describe arises from 17/?-hydroxy¬ steroid dehydrogenase activity and part from a steroid 5aor 5/?-dehydrogenase.…”
Section: Histochemical Considerationsmentioning
confidence: 99%
“…Goldberg et al 1964, Ikonen 1965, Taki et al 1967. Goldberg et al 1964, Ikonen 1965, Taki et al 1967.…”
Section: Discussionunclassified
“…An even more striking example has been the common failure to detect this reaction in the Leydig cells of the normal primate testis (Goldberg, Jones & Turner, 1963;Maeir, 1965;Deane & Rubin, 1965). However, Goldberg, Jones & Borkowf (1964) have shown that hydroxysteroid dehydrogenase activity in the human testis can be demonstrated when sub¬ strates other than dha are employed, notably A4-3)3-hydroxysteroids.…”
Section: Discussionmentioning
confidence: 99%